STUDIES ON CORRELATION AND PATH ANALYSIS IN BRINJAL (SOLANUM MELONGENA L.) GENOTYPES - DIVYA ARTI; A. K. SHARMA; SHILPI KHAR (The Bioscan, 2019)
Genetic studies in terms of correlation and path coefficients analysis were studied for twelve horticulture traits in fifty diverse genotypes of brinjal. The results indicated that yield per plant had significant positive association with number of marketable fruits per plant (0.693, 0.653), ascorbic acid content (0.290, 0.271), total harvest duration (0.278, 0.259), fruit weight (0.273, 0.238), fruit breadth (0.203, 0.160) and fruit length (0.163, 0.164) whereas, negative correlation were observed with days to first harvest (-0.502, -0.428), days to 50 per cent flowering (-0.323, -0.273) and plant height (-0.319, -0.279). Therefore main emphasis should be given on these characters, while making selection in brinjal genotypes. The path coefficient analysis revealed that the high positive direct effect towards fruit yield per plant was contributed by marketable fruit number per plant (0.777), fruit weight (0.277), fruit breadth (0.234) and fruit length (0.167) at phenotypic level. Thus, indicating direct selection for these traits as a criterion for yield improvement in brinjal.